Immediate Complete Overdenture: optimizing patient’s quality of life with endodontic - prosthodontic approach - Kuntjoro, Mefina; Agustono, Bambang; Laksono, Harry; Kamadjaja, Michael Josef Kridanto; Mundiratri, Karina; Kurdi, Abil; Fitriana, Astila; Faidah, Faidah; Prasetyo, Eric Priyo (Conservative Dentistry Journal, 2024)
Background: Immediate complete overdentures are designed for placement denture immediately following the extraction or decapitation of natural teeth. This procedure overcome the challenges associated of esthetic problems, including functional difficulties and psychological issues. Purpose: The article aims to highlight the advantages of endodontic-prosthodontic approach through immediate overdenture, such as the preservation of alveolar bone and improvement in patient’s psychological well-being and quality of life. Case: A 60-years-old female came into Universitas Airlangga Dental Hospital with the chief complaint of missing multiple teeth with upper front teeth becoming loose and desire to replace them because of difficulty in chewing food. Case Management: Diagnostic impressions were taken using irreversible hydrocolloid material, then poured in the dental stone to create final impression. The treatment plan included endodontic treatment, scaling and root planning for 11. The vertical dimension of occlusion was established using a bite rim and mounted on an articulator. Then, the immediate overdenture was created by arranging artificial teeth. Before the denture insertion, 11 was decapitated and filled the orifice with glass ionomer cement. Extraction of 21, 22, 23 was carried out and after ensuring hemostasis, the immediate overdenture was inserted. To finalize the denture insertion, occlusion was assessed using articulating paper. Control was done after day 1,3 and 7 after denture insertion. Conclusion: This case report describes the effectiveness of immediate overdentures as a valuable treatment option through endodontic-prosthodontic approach. By providing a functional and aesthetic solution while minimizing the edentulous period, immediate dentures significantly enhance patient’s quality of life.